Florística e fitossociologia em floresta ripária de Cerrado na Estação Ecológica de Uruçuí-Una, Piauí, Brasil. - Lopes, Marcelo Sousa (2016)
The riparian forest is characterized by being associated with watercourses, and despite representing small portion of the Cerrado, stands out mainly for its role in the protection of water resources. Many of these forests are protected in areas, as Uruçuí-Una Ecological Station (UUES), which has a 135,000 ha area in Cerrado phytogeographical domain, located in Baixa Grande do Ribeiro-PI municipality, Northeast of Brazil. In order to contribute to the floristic and phytosociology knowledge of Piauí state riparian forests, a study was developed on the banks of Uruçuí-Preto River in the UUES, where they were deployed 10 permanent 20 x 50 m plots, all parallels to the river and equidistant 50 m, totaling one hectare (1ha) in sampling area. All trees and shrubs individuals, were collected within and between plots, as well as about 10 meters above and after their transects. Within the plots, demarcated to all individuals with PBH (perimeter at breast height = 1.30 m above ground level) > 10cm, also was estimated each individual height. The samples collected were properly herborized, identified taxonomically and maintained in herbarium Graziela Barroso (TEPB) and Delta do Parnaíba (HDELTA). The results showed 90 species, 71 genus and 37 families with a greater richness associated to Leguminosae (17 species), Rubiaceae (10), Chrysobalanaceae (5), Vochysiaceae (5), Bignoniaceae (4), Melastomataceae (4), Arecaceae (3), Anacardiaceae (3) and Annonaceae (3). Regarding the diversity of species, Shannon index (H ') was 3.85 nats / ind-1, indicating a high biological diversity in the location and Pielou?sevenness index (J') was 0.81, indicating that the species are well distributed in this plant community. Total basal area was 22.70 m2ha-1 and total absolute density 1.973 ind ha-1, with 8.93cm mean diameter and 68.43cm maximum diameter assigned to an individual Vochysia pyramidalis. This specie also stood out with the highest importance value (VI) and high frequency (90%), followed by Mauritia flexuosa and the category of deadindividuals . The heterogeneity of riparian forest in UUES and its constituent species, gathered similar characteristics to Semideciduous and Deciduous Forests, with representative characteristics of the first one, due phytosociological relations and the genus and species being, and the low deciduousness during the year.